2016
DOI: 10.1093/heapol/czw002
|View full text |Cite
|
Sign up to set email alerts
|

Motivating health workers up to a limit: partial effects of performance-based financing on working environments in Nigeria

Abstract: Background: In 2012, the Nigerian government launched performance-based financing (PBF) in three districts providing financial incentives to health workers based on the quantity and quality of service provision. They were given autonomy to use funds for operational costs and performance bonuses. This study aims to understand changes in perceived motivation among health workers with the introduction of PBF in Wamba district, Nigeria. Methods: The study used a qualitative research design to compare perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 26 publications
8
61
0
Order By: Relevance
“…The effects of PBF-N have been partly determined by problems at the level of these other interventions. This dependence upon the whole health system has been documented in many PBF studies; barriers vary across experiences, but several of those reported in this study (competencies of human resources at the facility level, skills of supervisors, supply of inputs and delays in payment) have been reported in other experiences [50][51][52][53][54][55][56][57][58][59][60]. Such a dependence confirms the systemic nature of PBF [61], but at short term, it has an impact on the effectiveness of the strategy.…”
Section: Discussionsupporting
confidence: 68%
“…The effects of PBF-N have been partly determined by problems at the level of these other interventions. This dependence upon the whole health system has been documented in many PBF studies; barriers vary across experiences, but several of those reported in this study (competencies of human resources at the facility level, skills of supervisors, supply of inputs and delays in payment) have been reported in other experiences [50][51][52][53][54][55][56][57][58][59][60]. Such a dependence confirms the systemic nature of PBF [61], but at short term, it has an impact on the effectiveness of the strategy.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed evidence from other systematic reviews and global health studies confirms that the performance, attrition and retention of frontline HCWs are linked to intrinsic and extrinsic motivational factors such as being proud of their contributions to communities, opportunities for skills improvement and self-development, supportive supervision, proper remuneration, and healthy organizational cultures and work environments [48][49][50]. Some recent studies, for example, highlight opportunities to motivate health care providers in terms of performance-based incentives [51,52] and team-based goals and incentives model [50].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also question whether this benefit has affected the quality of care in other areas not targeted by the program, whether it has been effective to improve performance or can be considered essential for the maintenance of the quality of care itself. In different ways, these questions are made in both high income (Forbes, Marchand, & Peckham, 2016;Peckham & Wallace 2010;Roland & Guthrie, 2016) and middle and low income countries (Bhatnagar & George, 2016;Lee et al, 2012). Findings have also revealed, in this case related (possibly) more to middle and low income countries, that workers and managers were not fully aware of performance indicators and standards.…”
Section: Contributions From Global Health and Public Policymentioning
confidence: 99%